Radio‐guided vs clip‐guided localization of nonpalpable mass‐like lesions of the breast from a screened population: A propensity score‐matched study. Issue 7 (11th February 2019) - Corsi, Fabio; Bossi, Daniela; Combi, Francesca; Papadopoulou, Ourania; Amadori, Rosella; Regolo, Lea; Trifirò, Giuseppe; Albasini, Sara; Mazzucchelli, Serena; Sorrentino, Luca
Abstract: Background and Objectives: An accurate localization is mandatory to tailor breast lumpectomy in nonpalpable cancers. The aim of this study was to compare radio‐guided localization (ROLL) vs ultrasound localization of a titanium clip with collagen (TCC) in nonpalpable mass‐like breast cancers. Methods: Two hundred seventy‐three consecutive patients were reviewed: 64 patients were localized by TCC and 209 patients by ROLL. Propensity score‐matched analysis was performed. Margin status and reintervention rates were compared. Adequacy of resection was expressed as the calculated resection ratio (CRR) considering lesion size. Loco‐regional and distant recurrence rates were assessed with ROLL vs TCC. Results: No differences were found with ROLL vs TCC in clear margins (90.6% vs 89.1%; odds ratio, 0.74; P = 0.64) or reoperations (6.7% vs 1.6%; P = 0.529). ROLL allowed more tailored resections compared with TCC (adjusted CRR, 1.7 vs 2.7; P = 0.0008), particularly in lesions with associated extensive intraductal component (CRR, 3.0 vs 4.5; P = 0.017). Loco‐regional recurrence occurred in 1.9% of ROLL patients vs 3.2% of TCC cases ( P = 0.628). Conclusions: ROLL and TCC are equally effective to excise nonpalpable mass‐like breast cancers with clear margins, providing similar loco‐regional control. However, ROLL allows more tailored breast resections, particularly in lesions with the associated extensive intraductal component.